2006
DOI: 10.1021/nl060992s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aggregation Kinetics on the Thermal Conductivity of Nanoscale Colloidal Solutions (Nanofluid)

Abstract: The thermal conductivity, k, of nanoscale colloidal suspensions (also known as nanofluid), consisting of nanoparticles suspended in a base liquid, is much higher than the thermal conductivity of the base liquid at very small volume fractions of the nanoparticles. However, experimental results from various groups all across the world have shown various anomalies such as a peak in the enhancement of k with respect to nanoparticle size, an increase as well as a decrease in the ratio of k of these colloidal soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
370
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(409 citation statements)
references
References 30 publications
15
370
2
7
Order By: Relevance
“…It is observed that heat conductivity first increases linearly with the degree of agglomeration, reaches a maximum at the percolation threshold and finally decreases. The raising of conductivity with size (at nanoscale) was confirmed by many authors [46][47][48][49][50][51] in the case of epoxy resin with various fillers and by Prasher et al [31,52] in the case of nanofluids.…”
Section: Final Validation Of Dependence Of the Effective Thermal Condmentioning
confidence: 70%
“…It is observed that heat conductivity first increases linearly with the degree of agglomeration, reaches a maximum at the percolation threshold and finally decreases. The raising of conductivity with size (at nanoscale) was confirmed by many authors [46][47][48][49][50][51] in the case of epoxy resin with various fillers and by Prasher et al [31,52] in the case of nanofluids.…”
Section: Final Validation Of Dependence Of the Effective Thermal Condmentioning
confidence: 70%
“…The second mechanism stimulates phonons transference along large particles or particle aggregates, which involves that particles with large aspect ratio have better heat transfer properties Özerinç et al, 2010). As a result, the size and shape of nanoparticles and clusters formed are the key factors for the thermal conductivity enhancement Prasher et al, 2006;Shima et al, 2010;Warrier et al, 2010;Wu et al, 2010). It was demonstrated that chain-like structures and nanotubes or nanofibers provide the highest thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting phenomenon is that most of the viscosities are under-predicted by the traditional Einstein viscosity model [9,10]. This discrepancy could be caused by aggregation of the nanoparticles and an underestimated effective volume fraction of clusters [10,11]. Rubio-Hernandez et al…”
mentioning
confidence: 99%
“…Rooij et al [12] used the fractal model to analyze aggregation in a polymer dispersion and studied the shear viscosity. Prasher et al [10,11] and Jiang et al [13] studied the kinetic process of nanoparticle aggregation, in which fractal models were used to describe the structures of nanoparticle aggregates and were combined with the effective medium theory to predict their physical properties. For the kinetic model study, the formation process and structure of an aggregate are related to particle-particle interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation